2009
DOI: 10.1007/s12263-008-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A induces apoptosis in neuronal cells

Abstract: The mycotoxin ochratoxin A (OTA), which is produced by Aspergillus and Penicillium subspecies, is a frequently present contaminant of food and feedstuffs. OTA exhibits a wide range of toxic activities including nephro-and hepatotoxicity. However, little is known regarding potential neurotoxic effects of OTA. In the present study primary neurons as well as SH-SY5Y neuronal cells were incubated with increasing concentrations of OTA (0.1-2.5 lmol/L). OTA treatment resulted in a dose-dependent increase in cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 34 publications
4
57
0
5
Order By: Relevance
“…Ochratoxin A (OTA), one of the mycotoxins with greatest public health and agroeconomic significance [1][2][3], has been reported to be toxic to stomach, intestine, liver, kidney, neurons, and immune cells [2][3][4][5][6][7][8][9][10]. Ochratoxin A further has teratogenic potency [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A (OTA), one of the mycotoxins with greatest public health and agroeconomic significance [1][2][3], has been reported to be toxic to stomach, intestine, liver, kidney, neurons, and immune cells [2][3][4][5][6][7][8][9][10]. Ochratoxin A further has teratogenic potency [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ochratoxin intoxication may lead to anemia [13,14] with hypochromic-microcytic erythrocytes [13]. Ochratoxin A is in part effective by triggering apoptosis [5,6,9,10,[15][16][17][18][19][20][21][22][23][24][25][26]. Mechanisms involved in the stimulation of apoptosis by ochratoxin A include oxidative stress [18,27,28] and Ca 2+ entry [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of heavy metal and pesticides, both direct neurotoxicity and indirect neurotoxicity through alteration of glial functions have been demonstrated (Aschner, 2000;Franco et al, 2010;Gaasch et al, 2007;Hazell, 2002). Previous studies have already shown that various fungal toxins or mycotoxins (mainly fumonisins, ochratoxins, and trichothecenes) are able to directly cause brain cell death (Belmadani et al, 1999;Bruinink et al, 1998;Corps et al, 2010;Islam et al, 2009;Kwon et al, 2000;Merrill et al, 1996;Osuchowski and Sharma, 2005;Pestka et al, 2008a;Purzycki and Shain, 2010;Sava et al, 2006;Zhang et al, 2009). However, only few evaluations have been conducted on the potential effect of mycotoxins on the functions of glial cells (Monnet-Tschudi et al, 1997;Razafimanjato et al, 2010;Zurich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ochratoxin exposure leads to mitochondrial impairment and bioenergetics compromise and a secondary increase in the production of ROS [296,298]. Such diminished mitochondrial performance is in part likely to be due to chronic oxidative stress, but the toxin also inhibits complex 1 of the electron transport chain and directly impairs mitochondrial membrane potential [299,300]. It is also of interest that exposure to ochratoxin A provokes atypical responses in microglia and astrocytes compromising their neuroprotective function and positively promotes neuroinflammation via the up-regulation of for example NF-ÎșB [301,302].…”
Section: Chronic Mold and Mycotoxin Exposurementioning
confidence: 99%